Cartels as Defensive Devices: Evidence from Decisions of the European Commission 2001-2010 - Herold, Daniel; Paha, Johannes (Review of Law and Economics, 2018)
Why would an industry that was not colluding yesterday start colluding today? This article distills insights about cartel formation from 41 cases prosecuted by the European Commission between 2001 and 2010. The case studies examine the events occurring prior to the cartels' set-up. Cartel formation is affected by changes in prices, demand and customer conduct, capacity utilization, increased imports and entry by competitors, as well as events in the legal and regulatory environment of the firms. Yet, none of these factors serves as a good marker of cartel formation when being regarded in isolation. It rather needs to be analyzed how changes in these factors interact and whether they raise the intensity of competition. In this context, factors that are commonly deemed to destabilize cartels, like entry of new competitors or buyer power, are found to actually foster cartel formation.
CRIS-Team Scopus Importer:2022-11-17
Keywords: cartel formation; case study; collusion